2019
DOI: 10.1515/jpem-2019-0358
|View full text |Cite
|
Sign up to set email alerts
|

Air occlusion in insulin pumps of children and adolescents with type 1 diabetes

Abstract: BackgroundInsulin pumps are a frequently used technology among youth with type 1 diabetes. Air bubbles within insulin pump tubing are common, preventing insulin delivery and increasing the risk of large glycemic excursions and diabetic ketoacidosis (DKA). We sought to determine the prevalence of air bubbles in insulin pump tubing and identify factors associated with clinically significant air bubbles.MethodsFifty-three subjects were recruited over 65 office visits. The insulin pump tubing was visualized, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…At least, the studies referred to below describe the clinical relevance of air bubbles in kids and adolescents. 3 A correlation between the number of air bubbles and the age of the study participants was observed. Also, patients with high insulin sensitivity might respond more rapidly to interruptions in insulin flow.…”
Section: Clinical Relevance Of Air Bubblesmentioning
confidence: 85%
See 1 more Smart Citation
“…At least, the studies referred to below describe the clinical relevance of air bubbles in kids and adolescents. 3 A correlation between the number of air bubbles and the age of the study participants was observed. Also, patients with high insulin sensitivity might respond more rapidly to interruptions in insulin flow.…”
Section: Clinical Relevance Of Air Bubblesmentioning
confidence: 85%
“…• • One study was conducted to evaluate how frequently air bubbles occur in insulin pump infusion lines and identify the factors that lead to clinically relevant air bubbles. 3 For this purpose, the authors recruited 53 children and adolescents with diabetes and visually observed their infusion sets. The length of all observed air bubbles was measured and converted to time without insulin delivery at the lowest basal rate.…”
Section: Publications About Air Bubblesmentioning
confidence: 99%